2022
DOI: 10.3390/s23010342
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Sharing in the Sky and Space: A Survey

Abstract: In order to achieve the vision of seamless wireless communication coverage, a space–air–ground integrated network is proposed as a key component of the sixth-generation (6G) mobile communication system. However, the spectrum used by aerial networks has become gradually crowded with the increase in wireless devices. Space networks are also in dire need of developing new bands to address spectrum shortages. As an effective way to solve the spectrum shortage problem, spectrum sharing between aerial/space networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
0
0
Order By: Relevance
“…Te study's fndings showed that the introduced technique, in the presence of a SNR, obtained the most intense detection speed of about 0.68, while KNN showed a recognition speed of 0.58 and OR rules are about 0.5, respectively. Research on the sharing of spectrum across aerial/space networks and ground networks was summarized by Zhang et al [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Te study's fndings showed that the introduced technique, in the presence of a SNR, obtained the most intense detection speed of about 0.68, while KNN showed a recognition speed of 0.58 and OR rules are about 0.5, respectively. Research on the sharing of spectrum across aerial/space networks and ground networks was summarized by Zhang et al [11].…”
Section: Related Workmentioning
confidence: 99%
“…(2) Valid User and MU as Output (3) for the y � 1 to n choice, (4) if public key is validated (5) if the private key is confrmed. (6) Valid User is discovered ( 7) else (8) MU is found (9) end if (10) end if (11) end for ALGORITHM 3: MU identifcation using digital signature verifcation.…”
Section: Mu Detectionmentioning
confidence: 99%
“…As a dynamic spectrum allocation system based on opportunistic access, cognitive radio provides a new solution to alleviate the problem of spectrum scarcity and has been widely applied in new-generation information technology fields, such as the Internet of Things [1], radar communication integration [2], unmanned aerial vehicle monitoring [3], and satellite communication [4]. Spectrum sensing is a prerequisite for the implementation of cognitive radio systems.…”
mentioning
confidence: 99%